KETERBACAAN BUKU TEKS PESERTA DIDIK TERBITAN KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN UNTUK KELAS V SEKOLAH DASAR - Dominika Catur Prabawati (Universitas Katolik Musi Charitas, 2019)
This study aims to describe the readability of the teks in the narrative essay contained in the text books published by the ministry of education and culture for grade V students. This study uses quantitative qualitative. Data collection techniquea in this study by collecting narrative text in the fifth grade students text books in the student text books there are 13 narrative text, to find out the level of readability of the narrative tekt in the fifth grade students books by culculating according to the steps of the formula fry chart. Based on the reselts of the discussion, it can be concluded that overall the narrative text in the fifth grade students text books has different readability reselts and the grade V student text books have a 31% readability level within the range of the fry graph located at class IV, V, VI with that student text books suitable for use in class V.